Common origin of sequential cutaneous CD30+ lymphoproliferations with nodal involvement evidenced by genome‐wide clonal evolution. Issue 4 (31st January 2019) - Xerri, Luc; Adélaïde, José; Avenin, Morgan; Guille, Arnaud; Taix, Sebastien; Bonnet, Nathalie; Carbuccia, Nadine; Garnier, Séverine; Mescam, Lenaïg; Murati, Anne; Chaffanet, Max; Coso, Diane; et al.
Abstract : Aims: This study sought to clarify the molecular pathways underlying the putative evolution from lymphomatoid papulosis (LyP) to cutaneous anaplastic large‐cell lymphoma (c‐ALCL) and lymph node invasion (LNI). Methods and results: We analysed nine sequential tumours from the same patient presenting with parallel evolution of LyP ( n = 3) and c‐ALCL ( n = 1) with LNI ( n = 1), combined with systemic diffuse large B‐cell lymphoma (DLBCL) ( n = 4). Clonality analysis showed a common clonal T‐cell origin in the five CD30+ lesions, and a common clonal B‐cell origin in the four DLBCL relapses. Array‐comparative genomic hybridisation and targeted next‐generation sequencing analysis demonstrated relative genomic stability of LyP lesions as compared with clonally related anaplastic large‐cell lymphoma (ALCL) tumours, which showed 4q and 22q13 deletions involving the PRDM8 and TIMP3 tumour suppressor genes, respectively. The three analysed CD30+ lesions showed mostly private (specific to each sample) genetic alterations, suggesting early divergence from a common precursor. In contrast, DLBCL tumours showed progressive accumulation of private alterations, indicating late divergence. Conclusions: Sequential cutaneous and nodal CD30+ tumours were clonally related. This suggests that LyP, c‐ALCL and LNI represent a continuous spectrum of clonal evolution emerging from a common precursor of cutaneous CD30+ lymphoproliferations. Therefore, nodal ALCL tumours in the context of LyP should be considered as a form of transformation rather than composite lymphoma.